Electrochemotherapy with bleomycin, oxaliplatin, or cisplatin in mouse tumor models, from tumor ablation to in situ vaccination - Uršič Valentinuzzi, Katja; Kamenšek, Urška; Kranjc Brezar, Simona; Heranney, Chloe; Komel, Tilen; Buček, Simon; Čemažar, Maja; Serša, Gregor (Frontiers in Immunology, 2025)
IntroductionIn addition to its direct cytotoxic effects, ablative therapies as electrochemotherapy (ECT) can elicit indirect antitumor effects by triggering immune system responses. Here, we comprehensively analyzed this dual effectiveness of intratumoral ECT with chemotherapeutic drugs bleomycin (BLM), oxaliplatin (OXA), and cisplatin (CDDP). Our aim was to determine if ECT can act as in situ vaccination and thereby induce an abscopal effect. By evaluating ECT’s potential for in situ vaccination, our goal was to pave the way for future advancements for its combination with emerging (immuno)therapies, leading to enhanced responses and outcomes.MethodsWe employed two mouse tumor models, the immunologically cold B16F10 melanoma and 4T1 mammary carcinoma, to explore both local and systemic (i.e., abscopal) antitumor effects following equieffective intratumoral ECT with BLM, OXA, and CDDP. Through histological analyses and the use of immunodeficient and metastatic (for abscopal effect) mouse models, we identified and compared both the cytotoxic and immunological components of ECT’s antitumor efficiency, such as immunologically recognizable cell deaths (immunogenic cell death and necrosis) and immune infiltrate (CD11+, CD4+, CD8+, GrB+).ResultsDifferences in immunological involvement after equieffective intratumoral ECT were highlighted by variable kinetics of immunologically recognizable cell deaths and immune infiltrate across the studied tumor models. Particularly, the 4T1 tumor model exhibited a more pronounced involvement of the immune component compared to the B16F10 tumor model. Variances in the antitumor (immune) response were also detected based on the chemotherapeutic drug used in ECT. Collectively, ECT demonstrated effectiveness in inducing in situ vaccination in both tumor models; however, an abscopal effect was observed in the 4T1 tumor model only.ConclusionsThis is the first preclinical study systematically comparing the immune involvement in intratumoral ECT’s efficiency using three distinct chemotherapeutic drugs in mouse tumor models. The demonstrated variability in immune response to ECT across different tumor models and chemotherapeutic drugs provides a basis for future investigations aimed at enhancing the effectiveness of combined treatments.